Pajak Penghasilan Atas Anak Angkat Yang Berpenghasilan - Suparna Wijaya; Annisa Febriana Safira (Politeknik Ganesha Medan, 2021)
Adoption have legal consequences for both adopted children, adoptive parents, and biological parents. The legal consequences can be seen in terms of civil law, customary law, islamic law, and also taxes. In civil law, customary law, and also islamic law, the legal consequences of adopting a child are related to the inheritance rights of an adopted child. Meanwhile, in tax the legal consequences of adopting children are related to Non-Taxable Income (PTKP) and the income of adopted children. Provisions related to inheritance rights for adopted children are very clear in the three laws, but the provisions regarding PTKP and the income of adopted children in taxes are not so clear. Based on the results of the study, it was found that there were still differences of opinion regarding PTKP and the income of adopted children. Differences related to PTKP arise when the adopted child has earned income, where the majority of interviewees argue that the adopted child can still be counted as PTKP of his adoptive parents and for the imposition of taxes on the income of the adopted child it is also combined with the adoptive parents. However, there is a opinion that when the adopted child has earned income, it will be counted as PTKP of the biological parents and for the imposition of taxes on the income of the adopted child it will also be combined with his biological parents.